Teacher satisfaction and its influence on job performance at the Language Center of the Jorge Basadre Grohmann National University in Tacna, in 2014. - Linares Dávalos, Rey Ángel (2015)
Objective: The research's main objective was to determine the influence of teacher satisfaction with job performance in the Language Centre of the National University Jorge Basadre Grohmann Tacna Tacna in 2014. Method: The field work included teaching the population, ie 45 people. The research was applied, descriptive and correlational features (since they allow existing models to make a descriptive analysis of the behavior of the variables, and then relate them used); The research design was not experimental, whose collection of information was crosssectional (given that some recommendations were made and the data were collected at a point in time). Results: We found that there is no significant influence of teacher satisfaction with job performance. In addition, staff believes that is characterized by an acceptable level of satisfaction; the most prominent indicator was the "Monitoring", with areas for improvement "just rewards" and "working conditions". Conclusions: The staff believes that its level of performance in their academic work are outstanding, the indicator highlighted was the "student satisfaction", being the aspects to improve the "teamwork" and "personal growth